ANALISIS KUALITAS LAYANAN TERHADAP LOYALITAS MELALUI KEPUASAN KONSUMEN PENGGUNA JASA TRANSPORTASI KRL COMMUTER LINE - Farhan Atha Syarif; Alfatih S. Manggabarani (Jurnal Akuntansi dan Pajak, 2022)
This study uses quantitative methods because to determine the effect of service quality and customer satisfaction on the loyalty of KRL Commuter Line users in DKI Jakarta. KRL Commuter Line is the mainstay of transportation for DKI Jakarta residents. The population of this research is the KRL Commuter Line users in DKI Jakarta. The number of samples used is 100 respondents with purposive sampling method and distributing questionnaires through google form. The analysis technique uses descriptive and inferential analysis with SmartPLS 3.2.9 software. The results of R Square Adjusted for the consumer satisfaction variable are 0.734 or 73.4% and the consumer loyalty variable is 0.606 or 60.6%. The results of hypothesis testing are (1) service quality has a positive and significant effect on customer satisfaction with a value of 0.859, (2) customer satisfaction has a positive and significant effect on consumer loyalty with a value of 0.505, (3) there is a positive and significant effect on service quality on consumer loyalty with value of 0.306, and (4) service quality through satisfaction has a positive and significant effect on consumer loyalty with a value of 0.434.